The Influence of Financial Literacy and Financial Attitude on Personal Financial Management: Pengaruh Financial Literacy, Financial Attitude terhadap Pengelolaan Keuangan Pribadi - Rahmah, Nur; Idris, Munadi; Salehaman; Imran, Muhammad (IAIN Kendari, 2025)
This study aims to examine the impact of financial literacy and financial attitudes on students' personal financial management. The position of this research is important because good financial literacy and financial attitudes can prevent students from excessive consumer behavior and improve their financial stability. The method used was the distribution of questionnaires to 100 students, employing Multiple Linear Regression Analysis with stages including classical assumption testing, t-test hypothesis testing, and F-test hypothesis testing. The results show that both financial literacy and financial attitudes have a significant effect on students' personal financial management, contributing new insights into the development of understanding the importance of these two factors in achieving better financial management. The implications of this study suggest that the development of financial literacy and positive financial attitudes should be a priority in higher education, particularly in the field of finance, to help students achieve more stable and sustainable personal financial management.